2009
DOI: 10.1073/pnas.0906361106
|View full text |Cite
|
Sign up to set email alerts
|

A circadian clock in macrophages controls inflammatory immune responses

Abstract: Time of day-dependent variations of immune system parameters are ubiquitous phenomena in immunology. The circadian clock has been attributed with coordinating these variations on multiple levels; however, their molecular basis is little understood. Here, we systematically investigated the link between the circadian clock and rhythmic immune functions. We show that spleen, lymph nodes, and peritoneal macrophages of mice contain intrinsic circadian clockworks that operate autonomously even ex vivo. These clocks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

37
675
4
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 682 publications
(743 citation statements)
references
References 45 publications
37
675
4
6
Order By: Relevance
“…For example the macrophage response to Salmonella is decreased in mice with an inactive clock gene (Bellet et al, 2013), and the extent of secretion of TNF and IL-6 by LPS stimulated macrophages follows a circadian rhythm (Keller et al, 2009). Besides effects of the circadian system on the immune response, the immune system also influences the circadian clock.…”
Section: Abnormal Clock Gene System In Autoimmune Diseases and Depresmentioning
confidence: 99%
“…For example the macrophage response to Salmonella is decreased in mice with an inactive clock gene (Bellet et al, 2013), and the extent of secretion of TNF and IL-6 by LPS stimulated macrophages follows a circadian rhythm (Keller et al, 2009). Besides effects of the circadian system on the immune response, the immune system also influences the circadian clock.…”
Section: Abnormal Clock Gene System In Autoimmune Diseases and Depresmentioning
confidence: 99%
“…Authors have shown that macrophages secrete cytokines based on a circadian clock in mice. 20 A circadian-dependent secretion could have influenced the levels found in SCI patients and account for the variability of our results, although more investigation of this topic in humans is needed.…”
Section: Discussionmentioning
confidence: 85%
“…This last point raises the role of circadian clock mechanisms in rhythmic immune functions that are now the subject of extensive investigation. Recent studies have shown that in mice, an endogenous clock can influence the daily oscillations in innate immune functions, like bacterial endotoxin-stimulated TNF-α and IL-6 secretion by isolated spleen cells (Keller et al, 2009) or phagocytosis in macrophages (Hayashi et al, 2007). These circadian clock mechanisms, which can operate autonomously even ex vivo in the spleen and lymph nodes, are based on the expression of major clock genes, like Bmal, Per, Clock and Rev-erb α (Keller et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that in mice, an endogenous clock can influence the daily oscillations in innate immune functions, like bacterial endotoxin-stimulated TNF-α and IL-6 secretion by isolated spleen cells (Keller et al, 2009) or phagocytosis in macrophages (Hayashi et al, 2007). These circadian clock mechanisms, which can operate autonomously even ex vivo in the spleen and lymph nodes, are based on the expression of major clock genes, like Bmal, Per, Clock and Rev-erb α (Keller et al, 2009). Moreover, clock gene expression in human immune cells seems to be very sensitive to a damaging challenge, since a single injection with endotoxin was found to suppress the expression of these genes in the PBLs of healthy humans volunteers (Haimovich et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation